Evaluation of Online Learning in Vocational High School Major in Accounting and Financial Institution: Kirkpatrick’s Model - Sriwidayati, Ninik; Widiyanti, Widiyanti; Zahro, Siti (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2022)
Online learning during the pandemic of COVID-19 in accounting and financial institution major of Public Vocational High School 1 of Boyolangu has not been evaluated as yet, which makes the effect and result of the learning still unknown; therefore, this research aimed to evaluate the online learning established at the school. The model of evaluation adopted in this research was Kirkpatrick’s two levels of evaluation: reaction and learning. The purposes are to measure students’ satisfaction with the online learning and understanding of subject materials given during the online learning. The data in this research were collected through questionnaires. The research found that students on the whole felt satisfied with the establishment of online learning during the pandemic for at least two reasons: students began to feel comfort and used to online learning and the information technology skills of both teachers and students improved by virtue of online learning. However, there were some problems which impaired the effectiveness of online learning, including limited internet quota and poor internet connection. Additionally, students had difficulty completing practical assignments because some of them did not possess laptops, and sometimes teachers had not given them any explanation of the subject materials before